Mapping the Research on Sustainable Finance: Bibliometric Insights from Web of Science and Scopus - Judijanto, Loso (West Science Business and Management, 2025)
This study presents a bibliometric analysis of sustainable finance research using data exclusively from the WoS and Scopus database and visualization via VOSviewer. The aim is to map the intellectual landscape, identify thematic clusters, and explore global collaboration patterns within this rapidly evolving field. Keyword co-occurrence analysis highlights "sustainable finance" as the central theme, surrounded by related concepts such as ESG, green finance, green bonds, and sustainable development goals. Temporal and density visualizations reveal a shift in focus from traditional sustainability issues to emerging topics like greenwashing, decentralized finance, and fintech. Author and country collaboration maps uncover influential scholars and strong regional networks, particularly among institutions in the United Kingdom, India, Germany, and Italy. While the field shows high growth and thematic diversity, it also displays gaps in methodological variety, geographic inclusion, and institutional integration. The findings contribute to a comprehensive understanding of sustainable finance research trends and provide directions for future interdisciplinary inquiry.